Debating the Greek 1940s: histories and memories of a conflicting past since the end of the Second World War - Avgeridis, Manos (Historein, 2017)
The article examines aspects of the long history of a major field of public debate in the second half of the twentieth century, that of the Greek 1940s, taking as its starting point the recent “history war” in Greece. It attempts to trace histories and memories from the immediate postwar years and to place them within a broader process: the historisation of the Second World War in Europe. In that context, the article begins by exploring one part of the initial efforts to form a European history of the resistance, from the perspective of the Greek case. Then, the focus is transferred to Greece, and to the mapping of a constellation of different memory and history communities, and the practices of history of the same period: the activities of veteran partisans and eye-witnesses with regard to their contribution to the formation of the first narratives on the war is a core issue at this level. Last, by following the developments in the academy and the politics of history during the Metapolitefsi, the focus returns to the current discussion, attempting a first approach to the subject through the strings that connect it with the past and, at the same time, as a debate of the twenty-first century.